Obraz heretyków w „Moralia in Iob” Grzegorza Wielkiego - Szram, Mariusz (Vox Patrum, 2019)
One of the key themes of the Moralia in Iob, or Gregory the Great’s commentary to the Book of Job, is the allegorical interpretation of Job’s three friends as heretics. Herewith the image of the heretics emerging from this work is not a historical presentation. Rather, it is a strongly rhetorical critical assessment of the phenomenon of heresy, enriched with analyzes and recommendations of a moral-spiritual nature. He addressed the issue of heresy for the most part due to apologetic motives, aiming at defending the orthodox faith. The image of the heretic has been strongly subdued to the process of rethoricization for this purpose. Frequent use of invective went hand in hand with a high degree of generality in the presentation of the personality and mode of operation of heretics. Gregory the Great hardly ever referred to specific figures of heretics and these were usually people of the past era, mainly the inventors of the great errors from the IVth and Vth centuries, like Arius or Eutyches. The portrayal of heretics as people characterized mainly by three vices – pride, hypocrisy and stupidity – assumes in Moralia a form of a topos, or a repetitive motif on a literary basis, appearing in the majority of early Christian anti-heretic texts. Admittedly, the most unique element in Gregory’s exegesis is the connection of the heretics’ traits of personality to the majority of the statements appearing in the book of Job. Only some of these allegories find their parallels in commentary on the book of Job attributed to Hieronim’s student, Philip Presbyter, whose work was most probably known to the Pope. Surely, Gregory encountered during his ministry the remainders of such earlier heresies as Arianism or Donatism, which could have led him to a wider reflection on the activities of heretics. However, it raises the question why in the late Christian antiquity, when the time for the emergence of great heretical movements passed, the critique of the heresy phenomenon became the main subject of the spiritual exegesis of the Book of Job.